Peran Kecerdasan Emosional Sebagai Mediator antara Mindfulnes dengan Motivasi Akademik Mahasiswa selama PJJ - Wilinda, Noveni; Salim, Rose Mini Agoes (Lembaga Penelitian dan Pengabdian Masyarakat UNJ dan Program Studi Psikologi Fakultas Pendidikan Psikologi Universitas Negeri Jakarta, 2023)
Academic motivation is an important factor that supports student success in their learning activities. This study aims to examine the role of emotional intelligence as a mediator in the relationship between mindfulness and academic motivation. The participants in this study were 161 undergraduate and postgraduate students doing distance learning. Data collection was carried out by distributing questionnaires online and the sampling technique used was convenience sampling. The measurement tools used are the Academic Motivation Scale (AMS), the Mindful Attention Awareness Scale (MAAS), and the Wong Law Emotional Intelligence Scale (WLEIS). The data obtained were analyzed quantitatively using the PROCESS v3.5 macro from the model Hayes 4. The results showed that emotional intelligence acts as a mediator in the relationship between mindfulness and academic motivation. Students' awareness of the